Celastrol: A Potential Natural Lead Molecule for New Drug Design, Development and Therapy for Memory Impairment - Muhamad Azrul, Amir Yusri; Mahendran, Sekar; Wong, Ling Shing; Gan, Siew Hua; Ravi, Subban; Vetriselvan, Subramaniyan; Nur Najihah, Izzati Mat Rani; Chidambaram, Kumarappan; Begum, M Yasmin; Ramar, Mohankumar; Sher Zaman, Safi; Siddharthan, Selvaraj; et al. (Dove Press, 2023)
Celastrol is a naturally occurring chemical isolated from Tripterygium wilfordii Hook. f., root extracts widely known for their neuroprotective properties. In this review, we focus on the efficacy of celastrol in mitigating memory impairment (MI) in both in vivo and in vitro models. Scopus, PubMed and Web of Science databases were utilised to locate pertinent literatures that explore the effects of celastrol in the brain, including its pharmacokinetics, bioavailability, behavioral effects and some of the putative mechanisms of action on memory in many MI models. To date, preclinical studies strongly suggest that celastrol is highly effective in enhancing the cognitive performance of MI animal models, particularly in the memory domain, including spatial, recognition, retention and reference memories, via reduction in oxidative stress and attenuation of neuro-inflammation, among others. This review also emphasised the challenges and potential associated enhancement of medication delivery for MI treatment. Additionally, the potential structural alterations and derivatives of celastrol in enhancing its physicochemical and drug-likeness qualities are examined. The current review demonstrated that celastrol can improve cognitive performance and mitigate MI in several preclinical investigations, highlighting its potential as a natural lead molecule for the design and development of a novel neuroprotective medication.